Career indecision among college students: a review of literature - Nasab, Mojgan Fadaei; Abdul Kadir, Rusnani (Faculty of Educational Studies, Universiti Putra Malaysia, 2009)
Educationally and vocationally undecided students have been of concern among counsellors, administrators and academic advisors at colleges and universities. Literature suggests that many practitioners view career indecision as a normal developmental task among students while others believe it is a serious and unhealthy issue. Undecided students may have mixed feelings of fear, anxiety, confusion, negative feelings and perception of themselves and their situation and are in need of professional help. Career indecision is a complex phenomenon. Counsellors need to understand this phenomenon so that they may be able to help adolescents and young adults in their career development. Extensive studies concerning the nature of career indecision among adolescents and young adults and factors related to it have been done. Various factors found to be related to career indecision such as self-perceptual problems, anxiety, personality disorders, parental and family interactions and expectations, and problems within the academic institutes including lack of proper information, knowledge, and guidance related to selecting a career. This paper presents a review of studies have been done on career indecision. The discussion focuses on the dimensions and typology of career indecision, factors related to it and implications to counsellors in helping increasing number of undecided students to obtain a clearer academic and career direction have been also discussed.